Is there any difference in the perception of the Airbnb brand gender across cultures? An exploration of gender and gender identity - Bongran Lucia Sun (Global Business & Finance Review (GBFR), 2022)
Purpose: This study explored the different perception of Airbnb's brand gender across cultures on the basis of gender and gender identity. Specifically, the objectives of this study are, first, to examine how users perceive Airbnb's brand gender; second, to explore the effect of gender and gender identity on brand gender; and finally, to observe the differences in perception of Airbnb's brand gender across cultures. Design/methodology/approach: The exploration was conducted by comparing two countries with different cultural backgrounds (American vs. Korean). Data was collected in the US and Korea. Amazon Mechanical Turk (Mturk)was used for the US sample. For the Korean sample, a research company specialized in online surveys was employed. Data were analyzed by SPSS, AMOS to test hypotheses. Findings: Gender identity fully affected brand gender for Americans, but for Koreans masculine gender identity (MGI) had an influence on the perception of masculine brand gender personality (MBP) and feminine gender identity (FGI) on the perception of feminine brand gender personality (FBP) only. Further, this study revealed that gender does not play a significant role in the relationship between gender identity and brand gender for the American group, while gender was found to be an important variable moderating the relationships for Koreans. In addition, the study showed that the impact of gender identity on brand gender is greater in the US than in Korea. Research limitations/implications: This study has several limitations. First, this study considered only two countries. More countries from different continents with diverse social backgrounds should be investigated to generalize the study results. Second, gender-related phenomena are multifactorial and involve several variables, including gender attitudes, gender role behaviors, and sexual orientation, therefore, future research may observe other gender-related variables. Third, there are questionable items in the measurement of brand gender. Future research may focus more on addressing this issue in the cross-cultural study of brand gender. Fourth, more in-depth insights into the role of gender identity will result if future research explores the relationship between Aaker's (1997) five brand personalities and gender identity. Finally, this study examined only one brand, Airbnb. Therefore, the results could be difficult to generalize and apply to other brands and industries. Future studies should focus on investigating the relationship between brand gender, identity, and gender in other brands in the hospitality industry. Originality/value: This study is one of few researches investigating the relationships between gender identity, gender, and brand gender across cultures. Therefore, the results of this study are expected to provide novel insights into brand strategies in marketing, both academically and practically, in terms of gender and gender identity market segmentation.
Keywords: 650; Brand gender personality; Gender; Gender identity; Cross cultural study; Gender equality paradox; Airbnb